Endoscopic Transorbital Approaches to Anterior and Middle Cranial Fossa: A Laboratory Investigation on Surgical Anatomy and Potential Routes - Nannavecchia, Beniamino A.; Ganau, Mario; Cebula, Hélène; Scibilia, Antonino; Bozzi, Maria T.; Zaed, Ismail; Gallinaro, Paolo; Boujan, Fazel; Dietemann, Jean-Louis; Djennaoui, Idir; Debry, Christian; Ligarotti, Gianfranco K.I.; Signorelli, Francesco; Proust, Francois; Chibbaro, Salvatore (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Transorbital neuroendoscopic (TONES) approaches promise to open up new horizons for skull base surgery, offering alternative routes to reach the anterior and middle cranial fossa (ACF and MCF, respectively).Objective The aim of this anatomical study is to acquire new surgical anatomy knowledge and exploit it for the refinement of TONES approaches, as an alternative to open surgery, to reduce the distance to the target, and the risk of neurovascular lesions in pathological conditions extending beyond the orbital cavity.Materials and Methods Six head specimens (12 orbits) were studied/dissected. The orbit was approached and divided in a four clockwise quadrants manner to simulate three transconjunctival routes: the precaruncular (PC), preseptal (PS), and lateral retrocanthal (LRC), and one transpalpebral route—the superior eyelid crease (SLC). The boundaries and the most important anatomical landmarks were identified and are herein duly detailed with particular attention to the neurovascular structures encountered in each of those routes.Results The dissections showed that the PC approach facilitates the treatment of optic nerve and frontal sinus pathologies, whereas LRC appears safer to reach ACF and MCF allowing for a free multiplanar working channel (up to 180 degrees) to the floor, roof, and lateral-to-medial walls.Conclusion The plane of tendon lateral canthal's insertion and the sphenofrontal suture (SFS) were identified as the key anatomical landmarks for TONES approaches. Further studies are warranted to establish a practical clinical algorithm based on the anatomical four clockwise quadrants herein implemented/proposed, and the key surgical landmarks identified.
Keywords: orbit; four clockwise quadrants; skull base; transorbital neuroendoscopic approaches; anterior cranial fossa; middle cranial fossa; sphenofrontal suture